ANTIBACTERIAL ACTIVITY AND HEMATOLOGICAL PROFILE OF RAT (Rattus norvegicus) DUE TO ADMINISTRATION OF ETHANOL EXTRACT OF SOURSOP FLOWERS (Annona muricata L.) AND Salmonella enteritidis INFECTION - Zuraidawati Zuraidawati; Sugito Sugito; Darmawi Darmawi; Taufiq Taufiq (Jurnal Kedokteran Hewan, 2020)
This study aimed to determine the antibacterial activity of soursop flower extract (Annona muricata L.) and hematological profile of rats (Rattus norvegicus) due to administration of soursop flower ethanol extract and Salmonella enteritidis infection. The concentrations of soursop flower ethanol extract used for the antibacterial activity test were 25%, 50%, 75%, 100%, with the antibiotic ampicillin 10 μg/disk was used s a positive control (PC) and dimethyl sulfoxide (DMSO) 10% as a negative control (NC). For examination of hematological features, 15 male rat aged two months were used. All rats were divided into 5 treatment groups, each consisting of three rats. The NC group was not given soursop flower ethanol extract and S. enteritidis infection. The PC group was not given soursop flower extract but was given S. enteritidis infection. Groups P1, P2, and P3 were given ethanol extracts of soursop flower at a dose of 0.18, 0.36, and 0.72 g/rat/day peroral for a week using gastric sonde. On the following day (after administration of soursop flower extract) the first blood drawing was performed. All rats, except NC group, were then infected with S. enteritidis intraperitonially at dose of 3x108 CFU/mL dose (0.5 mL McFarland). One week after being infected with S. enteritidis, a second blood drawing was performed. The results of the antibacterial activity test showed that there was no antibacterial activity was observed since no inhibition at various concentrations was formed. The administration of soursop flower extract at various dosage levels was able to maintain the number of leukocytes but reduced the number of erythrocytes, hemoglobin concentration, hematocrit value and the number of platelets in rats; whereas S. enteritidis infection decreased all the hematologic features of lab rats.